2009
DOI: 10.4028/www.scientific.net/amr.83-86.1165
|View full text |Cite
|
Sign up to set email alerts
|

Grain Refinement in Ferritic Stainless Steel Welds: The Journey so Far

Abstract: The ferritic stainless steel is a low cost alternative to the most often adopted austenitic stainless steel due to its higher strength, better ductility and superior corrosion resistance in caustic and chloride environments. However, the application of ferritic steel is limited because of poor ductility and notch impact toughness of its weld section with differential grain structures. Several techniques have been explored to control the grain features of the weld to minimize these problems. In the present effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Ferritic stainless steel has gained great popularity in the last decade, but its applications are still restricted due to postweld issues associated with the fusion welding process [4]. The main reason behind the poor weldability of ferritic stainless steel is the non-existence of any inter-phase, the occurrence of fully ferrite phase, and the coarsening of grains in the fusion zone and heat-affected zone during welding [1].…”
Section: Introductionmentioning
confidence: 99%
“…Ferritic stainless steel has gained great popularity in the last decade, but its applications are still restricted due to postweld issues associated with the fusion welding process [4]. The main reason behind the poor weldability of ferritic stainless steel is the non-existence of any inter-phase, the occurrence of fully ferrite phase, and the coarsening of grains in the fusion zone and heat-affected zone during welding [1].…”
Section: Introductionmentioning
confidence: 99%
“…Severe grain growth in the regions exposed to heat, absence of any interphase precipitations, and formation of fully ferrite structure during solidification of the weld pool leads to a reduction in ductility and toughness of FSS [12]. Amuda and Mridha [13] reported that a slow cooling rate during welding gave sufficient time for grains to elongate, which further affects the metallurgical and mechanical properties. Mohandas et al [14] compared the mechanical properties of a 3mm thick FSS weld joint using gas tungsten arc welding(GTAW) process and shielded metal arc welding (SMAW) process.…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steels are a group of engineering materials that have been used extensively owing to their properties, such as corrosion resistance and physical and mechanical properties www.videleaf.com [1,2]. Among the various types of stainless steels, austenitic and ferrite types are ones of the most widely used.…”
Section: Introductionmentioning
confidence: 99%